The Effect Of Earnings Per Share (Eps), Exchange Rate, Inflation, And Interest Rate On Stock Prices On Food And Beverage Companies Listed On The Indonesia Stock Exchange (Idx) 2018-2021 - Annisa Sifa Fauzia; Yolandafitri Zulvia (Financial Management Studies, 2022)
This study has the aim of analyzing the effect ofEPS,exchange rates, inflation, interest rates on stock prices in food and beverage companies on the Indonesia Stock Exchange in 2018-2021.The population in this study are food and beverage companies listed on the Indonesia Stock Exchange in 2018-2021. Furthermore, the sample in the study was determined using the methodpurposive sampling. The number of samples obtained is 96 data. The analytical method used is multiple linear regression analysis using the IBM SPSS Statistics 26 program. The results of this study conclude that EPS, exchange rates, inflation, interest rates affect stock prices. Partially EPS stocks have a positive and significant effect on stock prices, exchange rates have a positive and insignificant effect on stock prices, inflation has a positive and insignificant effect on stock prices, and interest rates have a negative and insignificant effect on stock prices of food and beverage companies. 2018-2021. With the coefficient of determination as much as 28.3% while 71.7% influenced by other factors outside the study.